2020
DOI: 10.3390/jcm9103350
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Perceived Stress Related to the Covid-19 Outbreak through Stable Psychological Traits and Machine Learning Models

Abstract: The global SARS-CoV-2 outbreak and subsequent lockdown had a significant impact on people’s daily lives, with strong implications for stress levels due to the threat of contagion and restrictions to freedom. Given the link between high stress levels and adverse physical and mental consequences, the COVID-19 pandemic is certainly a global public health issue. In the present study, we assessed the effect of the pandemic on stress levels in N = 2053 Italian adults, and characterized more vulnerable individuals on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
186
6
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(269 citation statements)
references
References 104 publications
(135 reference statements)
26
186
6
13
Order By: Relevance
“…This result is consistent with the findings of Planchuelo-Gómez et al [6], who observed an increase of 2.75 points on the Stress subscale, with an average score of 6.51 on the first survey and 9.26 on the second. Similar to depression levels, stress levels were associated with negative affect and detachment, in line with the results reported in our previous study and the existing literature [32]. Lastly, our findings indicated that, within our sample (which ranged in age from 18-70 years), young age was associated with increased stress.…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with the findings of Planchuelo-Gómez et al [6], who observed an increase of 2.75 points on the Stress subscale, with an average score of 6.51 on the first survey and 9.26 on the second. Similar to depression levels, stress levels were associated with negative affect and detachment, in line with the results reported in our previous study and the existing literature [32]. Lastly, our findings indicated that, within our sample (which ranged in age from 18-70 years), young age was associated with increased stress.…”
Section: Discussionsupporting
confidence: 92%
“…As a consequence of the disruptive effects of COVID-19 pandemic, screening for AF may become even more important in the next future. Indeed, COVID-19 caused a polarization of care on the various manifestation of SARS-CoV-2 infection and on its management [39][40][41] that coupled with the fear and psychological distress diffused within the population [42][43][44][45] led to a marked reduction in access to Emergency Departments for acute cardiovascular conditions, including new-onset AF [46][47][48][49][50]. Some data from large datasets indicate that the risk of undiagnosed AF during COVID-19 lockdown is associated with an increased occurrence of stroke, related to lack of anticoagulation in patients at risk [48], thus making of great clinical value any initiatives of opportunistic screening for detecting unknown and previously undetected AF.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies on the topic should focus on a more objective assessment performed by external observers for a longer period of time. As older age seems to be associated with lower perceived stress during COVID-19 outbreak among the general public [ 34 , 35 ], it would be interesting to determine whether these factors affect the compliance with safety regulations among HCW in the future. Another disadvantage of our study stems from the chosen methodology which does not enable us to estimate the true value of the response rate.…”
Section: Discussionmentioning
confidence: 99%